2016
DOI: 10.1002/path.4832
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the epigenetic regulation of tumours and their microenvironments: opportunities and problems for epigenetic therapy

Abstract: The tumour microenvironment plays an instrumental role in cancer development, progression and treatment response/resistance. Accumulating evidence is underscoring the fundamental importance of epigenetic regulation in tumour immune evasion. Following many pioneering discoveries demonstrating malignant transformation through epigenetic anomalies ('epimutations'), there is also a growing emphasis on elucidating aberrant epigenetic mechanisms that reprogramme the milieu of tumour-associated immune and stromal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 208 publications
0
61
0
1
Order By: Relevance
“…. A large body of evidence suggests that epigenetic mechanisms commonly altered during tumorigenesis also participate in tumor immune escape mechanisms by affecting tumor‐associated immune cells to establish and maintain an immunosuppressive tumor microenvironment (TME) …”
Section: Epigenetic Deregulation Of Antitumor Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…. A large body of evidence suggests that epigenetic mechanisms commonly altered during tumorigenesis also participate in tumor immune escape mechanisms by affecting tumor‐associated immune cells to establish and maintain an immunosuppressive tumor microenvironment (TME) …”
Section: Epigenetic Deregulation Of Antitumor Immunitymentioning
confidence: 99%
“…It appears that early hypomethylation of CTA promoters during tumorigenesis is responsible for their specific expression in neoplastic cells; nevertheless, some CTAs also are frequently hypermethylated in certain cancers. Accordingly, the treatment of cancer cells with DNMT and HDAC inhibitors, either alone or in combination, consistently enhances or restores TAA expression, thus eliciting effective antitumor immunity . In addition to TAA expression, an efficient antitumor immune response requires the expression of antigen‐presenting machinery (APM)‐related genes and or major histocompatibility complex class I (MHCI)‐related and MHCII‐related genes.…”
Section: Epigenetic Deregulation Of Antitumor Immunitymentioning
confidence: 99%
“…A retrospective analysis of 3954 patients in phase 2/3 trials of bortezomib for the treatment of multiple myeloma reported that bortezomib‐based treatment was associated with a low incidence of cardiac events . Epigenetic cancer therapy using histone deacetylase inhibitors is also emerging, as epigenetic gene silencing is a hallmark of cancer cells. Two important types of epigenetic changes are DNA methylation by DNA methyltransferases (DNMTs) and histone modification by histone deacetylases (HDACs) .…”
Section: Fda‐approved Mtts For Oncologymentioning
confidence: 99%
“…Epigenetic cancer therapy using histone deacetylase inhibitors is also emerging, as epigenetic gene silencing is a hallmark of cancer cells. Two important types of epigenetic changes are DNA methylation by DNA methyltransferases (DNMTs) and histone modification by histone deacetylases (HDACs) . DNMTs and HDACs have become attractive therapeutic targets, and several HDAC inhibitors e.g., Romidepsin, Belinostat, and Panobinostat, have been used in the clinic.…”
Section: Fda‐approved Mtts For Oncologymentioning
confidence: 99%
See 1 more Smart Citation